31
Аноним
Математика
04 июня 09:40

Приведите подобные члены: a) 18a^2b-4a^2b+6a^2b= b) 6a^8b^2+7a^8b^2+(-2)a^8b^2= d) 4b^3c^4+8b^3c^4-14b^3c^4=

Ответ или решение1

Приведем подобные члены и упростим выражение: 

a) 18 * a^2 * b - 4 * a^2 * b + 6 * a^2 * b = a^2 * b * (18 - 4 + 6) = a^2 * b * (14 + 6) = a^2 * b * 20 = 20 * a^2 * b; 

b) 6 * a^8 * b^2 + 7 * a^8 * b^2 + (-2) * a^8 * b^2 =   6 * a^8 * b^2 + 7 * a^8 * b^2 - 2  * a^8 * b^2 =   a^8 * b^2 * (6 + 7 - 2) = a^8 * b^2 * (6 + 5) = a^8 * b^2 * 11 = 11 * a^8 * b^2; 

d) 4 * b^3 * c^4 + 8 * b^3 * c^4 - 14 * b^3 * c^4 = b^3 * c^4 * (4 + 8 - 14) = b^3 * c^4 * (8 - 10) = b^3 * c^4 * (-2) = -2 * b^3 * c^4. 

0 / 10000
ВходРегистрация

Вход

или

Регистрация